Analysis of the Factors Affecting Customers’ Purchase Intention: The Mediating Role of Customer Knowledge and Perceived Value - Bhakar, Shailja; Bhakar, Shilpa; Dubey, Abhay (Advances in Social Sciences Research Journal, 2015)
Celebrity endorsers and product packaging are two most important factors in creating the brand identity and help in evaluating a products perceived value as well as increasing the knowledge about the product. This study was aimed at evaluating the effect of celebrity endorser and product packaging on purchase intentions taking customer knowledge and perceived value as mediating variables. The sample size was 150 respondents and the sample was identified through non probability quota sampling technique. Questionnaires were standardized using reliability and factor analysis. Results indicated celebrity endorser significantly effects purchase intention of shampoos directly as well as celebrity endorser, product packaging and customer knowledge effect perceived value as mediating variable in turn effecting purchase intentions. Customer knowledge is a lesser important variable in case of shampoos purchase intention. Keywords: celebrity endorser, product packaging, customer knowledge, perceived value and purchase intention